Desenvolvimento de filmes finos de organosilicone depositados a plasma para fotoproteção do polipropileno - Freitas, Amanda de Sousa Martinez (2019)
Polypropylene (PP) is a polymer used industrially on a large scale. However, the PP has limitations in external use due to its sensitivity to photodegradation, when exposed to the elements. This limits the options of use and reduces its useful life. The chemical deposition of plasma-assisted steam can produce thin films of organosilicon, which cover the polymer surface. These films can increase chemical and physical resistance and the resistance to the degradation, without interfering in aspects such as color and brightness, due to their transparency and nanometric. The polypropylene samples were treated by Plasma-enhanced chemical vapor deposition (PECVD), for the deposition of the films were used different combinations of gases, pressure, and power. Gas pressures between 0.046 and 0.172 Torr are used, which is composed of the mixture of oxygen, argon and acetylene gases in various combinations and always having the precursor gas HMDSO. Deposition times ranged from 15, 30, 45 and 60 minutes, with power ranging between 40 and 160W and radiofrequency of 13.56 MHz. The sample sets were exposed to ultraviolet light (UV-C) of fluorescent lamps, germicidal, 15W of power, emission maximum at 254 nm wavelength, for the time intervals of 48 to 196 hours. The samples were characterized by SEM, FTIR, UV-Vis, profile, contact angle and instrumented indentation test. The SEM results show a mechanical anchorage of the film in relation to the substrate, since the crackings of the virgin polypropylene presented a width between 3.5 and 5 micrometers and a length of several millimeters, the polypropylene covered with films of organosilicon presents cracks with width 0.5 to 1 micrometer and length of 2 to 5 micrometers. In addition to the reduction in crack size and the good adhesion of the film to the substrate, it was observed that the film remained mechanically adhered to the surface of the polymeric material even with PP photodegradation. The microscopic analysis of the photodegraded material showed similar morphology to the phenomenon of fibrillation, however without tension use by a tensile load as usual, but by the separation of the walls of cracks, which arose due to the decrease of volume caused by the crystallization that occurs on photodegraded polymer surfaces. Finally, the results demonstrate that plasma deposited organosilicon film on polypropylene can be used for the physical and chemical protection of the material at photodegradation. This leads to an increase in the life of the material, a lower detachment of photodegraded layers and possibly decrease the release of secondary microplastics, thus reducing the environmental impact.